The mood of Fudokan karate competitors during direct preparation for kata competition - Piepiora, P. A.; Kot, E.; Piepiora, Z. N.; Vveinhardt, J. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2026)
Background. Direct preparation for competition, which takes into account the individual needs and moods of karate practitioners, is of significant importance for their form in the main event. To date, there have been few studies in this area relating to the mental sphere of competitors.